Determination of the Reasons for Migration and Life Satisfaction of Health Workers Who Migrated from Turkey to United Kingdom - Sevim Şen Olgay; Seher Yurt (Association of Nurse Managers, 2023)
Aim: This research was carried out to determine the reasons for migration and the life satisfaction of health workers who migrated from Turkey to the UK. Method: The sample of the descriptive study consisted of 128 health workers who immigrated from Turkey to the UK. The research data were collected using the Sociodemographic Data Collection Form and the Life Satisfaction Scale. In the analysis of the data, descriptive statistics (percentage, arithmetic mean, standard deviation) and the Mann-Whitney U test were used. A P value of <.05 was considered statistically significant. Results: It was determined that the mean age of the participants was 41.20+-10.56 years, 28.1% were nurses, 89.8% were professionally satisfied in the UK and 95.3% were satisfied with their decision to live in the UK. It has been determined that 64.8% of the reasons for migration are political, 55.5% are concerns about the future, and 53.1% are economic. The mean score of the life satisfaction scale of the migrant health workers was found to be 4.33+-.61. Conclusion: The findings of the study showed that the push factors for migration from Turkey to the UK are political and economic concerns and concerns of the future, economic prosperity is the pull factor, and life satisfaction is high in the UK.